Exploring the Metabolic Syndrome Trend in Young Adults in COVID-19 ERA: Metabolic Syndrome Trend in Young Adults - Aziz, Zubia; Sohail , Arisha; Soban , Madiha; Shah , Syed Muhammad Huzaifah; Fatima, Fasiha; Haque, Zeba (Pakistan Journal of Health Sciences, 2023)
COVID-19 pandemic imposed sudden changes in lifestyle with consequent altered metabolic status. Metabolic Syndrome is described as an altered metabolic profile of insulin resistance, dyslipidemia, hypertension, and central obesity which raises type 2 Diabetes Mellitus and cardiovascular disease danger at an early age. Objective: To analyze COVID-19 era status of obesity, hypertension, impaired glucose tolerance, dyslipidemia and metabolic syndrome in young adults. Methods: This was a cross-sectional study. 245 university students of either gender with ages 19–25 years were included. The lipid profile, fasting blood sugar and serum insulin was performed by kit method. The insulin resistance was determined by calculating the ratio of fasting glucose to insulin. SPSS version number 24.0 was used to analyze the data. Results: Metabolic syndrome's prevalence in overweight and obese subjects was found to be 36%. The most prevalent risk factor of Metabolic syndrome was raised blood pressure (60%) followed by insulin resistance (57%) and dyslipidemia (40%). The positive coefficient correlations were found for all Metabolic syndrome risk factors in general except HDL. The multivariate regression analysis evidenced that the BMI and WHR were the significant predictors of Metabolic syndrome risk factors. Conclusion: The COVID-19 restrictions consequences call for an urgency to effectively address e metabolic and related problems, especially among young individuals.